2016
DOI: 10.1080/07399332.2016.1140768
|View full text |Cite
|
Sign up to set email alerts
|

Female children with incarcerated adult family members at risk for lifelong neurological decline

Abstract: A secondary analysis of data from adult female prison inmates in the mid-Atlantic United States defined relationships between having incarcerated adult family members during childhood and neurological outcomes. Of 135 inmates, 99(73%) had one or more incarcerated adult family members during childhood. Regression analyses revealed that having incarcerated adult family members was related to greater frequency and severity of childhood abuse and higher incidence of neurological deficits in adulthood, especially r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Although these results are novel in relation to ABI/TBI within a general population, these findings align with previous studies in female children, adults with severe mental illness and adult homeless population linking ACEs to risk for brain injury. [29][30][31] Data on individual ACEs and their association with ABI and TBI were provided. Findings revealed that five out of the eight ACEs examined were significantly associated with ABI, while four out of the eight ACEs (ie, sexual abuse, physical abuse, household on October mental illness and an incarcerated household member) were significantly associated with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Although these results are novel in relation to ABI/TBI within a general population, these findings align with previous studies in female children, adults with severe mental illness and adult homeless population linking ACEs to risk for brain injury. [29][30][31] Data on individual ACEs and their association with ABI and TBI were provided. Findings revealed that five out of the eight ACEs examined were significantly associated with ABI, while four out of the eight ACEs (ie, sexual abuse, physical abuse, household on October mental illness and an incarcerated household member) were significantly associated with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological histories were validated by neurological examinations for all subjects in this data set and data collection was consistent for all subjects. Neurological history and examination methods were validated by neurologists and have been described in our previous publications (Brewer-Smyth et al, 2004;Brewer-Smyth et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Neurological histories were validated by neurological examinations for all subjects in this data set and data collection was consistent for all subjects. Neurological history and examination methods were validated by neurologists and have been described in our previous publications (Brewer-Smyth et al, 2004; Brewer-Smyth et al, 2016). The purpose was to obtain examination evidence of conditions that may be more prevalent in violent versus nonviolent females and evidence to support histories provided by each inmate, such as neurological deficits and cranial–facial scars or palpable areas of skull damage consistent with self-reports of traumatic injuries and other neurological histories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation